Characteristics of Beef Sausage Mixed with Modified Bekasam Meat Fermented by Lactobacillus plantarum - G. L. Meristica; J. Gumilar; K. Suradi (Faculty of Animal Science, Bogor Agricultural University, 2020)
Bekasam is a fermented food from Indonesia that potentially improves the quality of sausage when incorporated in the ingredients. This research was aimed to study the chemical, microbial, and sensory characteristics of sausage made of various concentrations of beef and bekasam meat. The chemical, microbial and sensory characteristics of sausage were investigated using an experimental method in a completely randomized design with 5 treatments, namely T1 (100% beef); T2 (75% beef + 25% bekasam meat); T3 (50% beef + 50% bekasam meat); T4 (25% beef + 75% bekasam meat); and T5 (100% bekasam meat). Data analysis of chemical and microbial characteristics was subject to ANOVA and post-hoc Duncan test, while sensory characteristics were analyzed using Kruskal-Wallis test and The Mann-Whitney test. The results showed that the addition of bekasam meat into the sausage mixture significantly (p<0.05) decreased fat content and sensory characteristics (color, flavor, texture, and overall acceptability). Meanwhile, it increased total bacteria, E. coli and S. aureus inhibition in the sausage. In conclusion, bekasam meat fermented with L. plantarum showed probiotic potentials and could modify beef sausage production.